2023
DOI: 10.3390/cancers15061775
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review and a Taxonomy to Assess the Impact of Mobile Apps on Cancer Care Management

Abstract: Mobile Health (mHealth) has a great potential to enhance the self-management of cancer patients and survivors. Our study aimed to perform a scoping review to evaluate the impact and trends of mobile application-based interventions on adherence and their effects on health outcomes among the cancer population. In addition, we aimed to develop a taxonomy of mobile-app-based interventions to assist app developers and healthcare researchers in creating future mHealth cancer care solutions. Relevant articles were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Engagement rates with cancer-related digital interventions tend to be higher than in other populations, but high variability in engagement measures and intervention components and lack of a threshold for acceptable engagement make it difficult to compare findings across studies. Reviews of empirical studies using cancer-related digital interventions have reported use rates between 70% and 100% [ 64 , 65 ]. These high use rates contrast with the generally low engagement with mHealth apps reported for individuals with other health conditions [ 2 , 10 , 11 , 13 - 15 ] and suggest that people with cancer might be particularly inclined to improve their health and change certain health behaviors through mHealth apps.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement rates with cancer-related digital interventions tend to be higher than in other populations, but high variability in engagement measures and intervention components and lack of a threshold for acceptable engagement make it difficult to compare findings across studies. Reviews of empirical studies using cancer-related digital interventions have reported use rates between 70% and 100% [ 64 , 65 ]. These high use rates contrast with the generally low engagement with mHealth apps reported for individuals with other health conditions [ 2 , 10 , 11 , 13 - 15 ] and suggest that people with cancer might be particularly inclined to improve their health and change certain health behaviors through mHealth apps.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement rates with cancer-related digital interventions tend to be higher than in other populations, but high variability in engagement measures and intervention components and lack of a threshold for acceptable engagement make it difficult to compare findings across studies. Reviews of empirical studies using cancer-related digital interventions have reported use rates between 70% and 100% [64,65]. These high use rates contrast with the generally low engagement with mHealth apps reported for individuals with other health conditions [2,10,11,[13][14][15] and suggest that people with cancer might be particularly inclined to improve their health and change certain health behaviors through mHealth apps.…”
Section: Comparison With Prior Workmentioning
confidence: 98%